Gender-responsive sentencing for women defendants in Indonesia: Integrating living law and feminist legal reasoning - Abdul Mutalib; Pujiyono Pujiyono; Sukirno Sukirno; Rahmat Hi. Abdullah; Ota Musashi (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2026)
Women defendants in Indonesia frequently experience double victimization, functioning simultaneously as offenders and as victims of domestic violence, sexual exploitation, and economic pressure rooted in asymmetrical gender power relations. This study examines how living law, interpreted through constitutional values and feminist legal reasoning, can be operationalized to enable gender-responsive sentencing for women defendants in Indonesia. Using a normative-juridical method with statutory, conceptual, and doctrinal-analytical approaches, the study analyzes legal materials through grammatical, teleological, and systematic interpretation. The findings reveal three main points. First, Article 2 extends the principle of legality into a material dimension through a constitutional filter that ensures gender responsiveness and rejects discriminatory customary legal practices. Second, Article 54 provides space for gender-responsive sentencing by allowing consideration of women’s victimization and structural conditions. Third, the study develops a Gender-Responsive Living Law Model that integrates living law and feminist legal reasoning into a structured, measurable, and accountable judicial process. The study concludes that Articles 2 and 54 of the National Criminal Code provide a normative framework for gender-responsive sentencing through a constitutional filter against discriminatory practices. However, its effectiveness depends on the application of a structured and integrative model to ensure that judicial discretion remains measurable and accountable. This study contributes to gender and socio-legal studies by integrating living law and feminist legal reasoning into an operational framework for criminal adjudication in Indonesia.